Monthly trends and the corresponding altitudinal shift in the snowfall/precipitation day ratio - Serquet, Gaelle; Marty, Christoph; Rebetez, Martine (My University, 2013)
A better understanding of the impact of changing temperatures on snow amounts is very important for the ski industry, but it is difficult to measure, particularly at different times of the snow season and not only on an annual or seasonal basis. Here, we analyze the snow day vs precipitation day ratios on a monthly basis from November to April in Switzerland and at 52 meteorological stations located between 200 and 2,700 m above sea level over a 48-year time span. Our results show that the conditions measured in the 1960s in November and March correspond to the present ones in December, January, and February.